Measurement of the average lifetime of b-hadrons in Z decays - Dova, María Teresa (1998)
We present a measurement of the average b-hadron lifetime t at the eqey collider LEP. Using hadronic Z decays b collected in the period from 1991 to 1994, two independent analyses have been performed. In the first one, the b-decay position is reconstructed as a secondary vertex of hadronic b-decay particles. The second analysis is an updated measurement of t using the impact parameter of leptons with high momentum and high transverse momentum. The combined result is <mtext>τ</mtext><mtext>b</mtext><mtext>=[1549±9</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>(stat)</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>±15</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>(syst)]</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>fs</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>.</mtext> In addition, we measure the average charged b-decay multiplicity 〈nb〉and the normalized average b-energy 〈xE〉b at LEP to be <mtext>〈n</mtext><mtext>b</mtext><mtext>〉=4.90±0.04</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>(stat)±0.11</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>(syst),</mtext><mspace sp="1" width="2px" linebreak="nobreak" is="true"></mspace><mtext>〈x</mtext>E<mtext>〉</mtext><mtext>b</mtext><mtext>=0.709±0.004</mtext><mspace sp="0.2" width="2px" linebreak="nobreak" is="true"></mspace><mtext>(stat+syst).</mtext>